The Role Of Brand Love And Wom In Mediating The Influence Of Brand Experience On Repurchase Intention - Tita Lattifia; I Gusti Ngurah Jaya Agung Widagda; I Gusti Ayu Ketut Giantari; Ni Ketut Seminari (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The research adopts the Stimulus-Organism-Response (SOR) theory as the grand framework to explain the relationships between the studied variables. The study was conducted on Larissa skincare customers in Denpasar using a quantitative approach with a survey method involving 145 respondents who are active customers and meet the criteria of making at least two repeat purchases in the past six months. The sample size was determined using the Slovin formula, and the sampling technique employed was simple random sampling. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that brand experience does not have a significant direct effect on repurchase intention, but it has a significant positive effect on both brand love and word of mouth. Furthermore, both brand love and word of mouth have a significant positive influence on repurchase intention. These findings indicate that the effect of brand experience on repurchase intention is indirect and fully mediated by brand love and word of mouth. This study is expected to contribute theoretically to the development of the Stimulus-Organism-Response (SOR) framework, particularly in the context of forming repurchase intention through consumers' psychological mechanisms. In practical terms, the findings also offer valuable insights for companies to formulate more targeted marketing strategies. By strategically managing brand experience, strengthening emotional attachment through brand love, and encouraging positive consumer communication via word of mouth, companies can enhance customer loyalty and promote sustainable repurchase behavior.